Masterful Care of the Aging Athlete A Clinical Guide (Springer International Publishing, 2018)
This unique text focuses exclusively on the ever-growing population of aging and masters athletes, both professional and amateur, presenting both operative and nonoperative management strategies for the range of sports-related injuries. The book is thematically divided into three sections. Part I describes the science of musculoskeletal aging and the benefits of remaining active as we age, including proper nutrition, supplements and medical therapies and adjuvants. Injuries common to the masters athlete are presented in part II, from the upper and lower extremities to the hips and spine, with special considerations for these injuries and treatments noted. Recommendations for how to thrive as a masters athlete comprise the final section, including return to sport, injury prevention and exercise as medicine. An ideal resource for clinicians who treat active adults who won't slow down, Masterful Care of the Aging Athlete is a compilation of clinical, technical and research approaches aimed at keeping active people moving, returning them to sport rapidly and durably and protecting them from a sedentary lifestyle.